Supramolecularly interacting polyurethane, polyurethane-based solid-state ionically conductive elastomer, and preparation method and application thereof

CN123003833APending Publication Date: 2026-10-30TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611507176.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

该专利中仅将碳纳米管作为导电填料与热塑性聚氨酯进行简单的熔融共混加工,虽然能够显著提高材料的电导率,而且有利于增强聚氨酯基体的绝对机械拉伸强度,但会由于未引入能够协同耗散能量的超分子错配网络,使得产品的在使用过程中,会因刚性填料引起的过度结合导致材料脆性增加,易在承受大应变受力时发生不可逆的分子链滑移,以致产品的弹性回复能力及动态环境下的导电稳定性大幅下降,产品长期使用的服从性及抗损伤性能差

Benefits of technology

(1)本发明模拟贝壳珍珠层刚柔并济的结构特征,通过刚性、柔性链延伸器交错引入体系,在空间几何构型、空间位阻及氢键配对间距上形成显著的超分子错配效应,诱导聚氨酯硬段相形成高度分散的纳米级微相分离结构。其中,刚性扩链剂含双苯环结构,依托APBIA分子中苯并咪唑稠环与独立苯环构筑扩展离域π电子共轭体系,可实现强烈的分子间π-π堆积作用,并与刚性氢键形成协同作用,共同稳定材料骨架结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003833A_ABST
    Figure CN123003833A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of high-performance polymer material synthesis, in particular to a supramolecular interaction polyurethane, a polyurethane-based solid-state ion conductive elastomer and a preparation method and application thereof. The supramolecular interaction polyurethane comprises the following raw materials in proportion by weight: 50-200 parts of polyglycol, 100-400 parts of diisocyanate, 10-200 parts of flexible hydrazide chain extender, 2-(4-aminophenyl)-5-aminobenzimidazole 10-200 parts of rigid chain extender, 1-20 parts of catalyst and 200-500 parts of anhydrous organic solvent; wherein the polyglycol comprises polyglycol A and polyglycol B. The required raw materials of the polyurethane-based solid-state ion conductive elastomer are proportioned by weight as follows: 100 parts of the supramolecular interaction polyurethane, 10-150 parts of lithium salt and 150-250 parts of anhydrous organic solvent. The supramolecular interaction polyurethane prepared by the application has high strength, high toughness, high elastic recovery capacity and excellent damage resistance, and the polyurethane-based solid-state ion conductive elastomer has sensitive, stable conductive sensing characteristics and an ultralow detection limit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-performance polymer material synthesis technology, and in particular to a supramolecularly interacting polyurethane, a polyurethane-based solid ion-conducting elastomer, and their preparation methods and applications. Background Technology

[0002] With the explosive growth of the Internet of Things, human-computer interaction, and personalized smart healthcare, flexible wearable devices integrating sensing, actuation, and human-computer interaction are becoming an important development direction for next-generation digital healthcare and rehabilitation assistive systems. Traditional rigid electronic devices and electromechanical exoskeletons have mechanical moduli far exceeding those of human soft tissue, generally suffering from poor wearing comfort, insufficient motor coordination, and low long-term use compliance. In recent years, emerging technologies such as soft robotics and flexible electronics have provided new ideas for constructing highly compliant, biocompatible wearable medical devices with good signal transmission capabilities. However, existing flexible devices often face the contradiction of balancing material strength and flexibility, easily exhibiting structural relaxation and signal attenuation under long-term cyclic loading. Therefore, constructing a functional elastomer material system that combines high elastic recovery capability, adjustable mechanical response, and stable signal transmission characteristics is key to advancing fully soft wearable devices.

[0003] Chinese invention patent application No. 202510467062.1 discloses a method for preparing a flexible sensing material of polyacrylamide / polyurethane composite conductive hydrogel. The conductive hydrogel is prepared using a polyacrylamide / polyurethane composite hydrogel as a flexible substrate and polyaniline as a conductive material. This patent application merely physically disperses and mixes the conductive polymer and the composite hydrogel. While this achieves a lower mechanical modulus and improves the wearing comfort of the wearable sensor against the skin, the lack of a strong, dynamic cross-linked network at the molecular level makes it difficult to balance mechanical strength and flexibility during use. Under prolonged cyclic loading from human movement, structural relaxation and damage to conductive pathways can occur, leading to severe attenuation of the sensing signal and a short product lifespan.

[0004] Chinese invention patent application number 202610433280.8 discloses a composite film based on modified carbon nanotubes and thermoplastic polyurethane, its preparation method, and its application. The polyurethane / carbon nanotube composite conductive elastomer achieves a stable bond between tannic acid and carbon nanotubes through a multi-step reaction, while simultaneously constructing a three-dimensional cross-linked network between the matrix and the filler, realizing a flexible strain sensor with multi-performance synergistic integration. This patent only uses carbon nanotubes as conductive fillers in a simple melt-blending process with thermoplastic polyurethane. Although this significantly improves the material's conductivity and enhances the absolute tensile strength of the polyurethane matrix, the lack of a supramolecular mismatch network capable of synergistic energy dissipation leads to increased brittleness due to over-bonding caused by the rigid filler during use. This makes the material prone to irreversible molecular chain slippage under high strain stress, resulting in a significant decrease in the product's elastic recovery ability and conductivity stability under dynamic environments, leading to poor long-term performance and damage resistance. Summary of the Invention

[0005] The purpose of this invention is to provide a supramolecularly interacting polyurethane, a polyurethane-based solid ion-conducting elastomer, its preparation method and application. The supramolecularly interacting polyurethane has high strength, high toughness, high elastic recovery ability and excellent damage resistance. At the same time, the solid ion-conducting elastomer obtained based on the supramolecularly interacting polyurethane has sensitive and stable conductive sensing characteristics and ultra-low detection limit.

[0006] The objective of this invention can be achieved through the following technical solutions: One of the objectives of this invention is to provide a supramolecularly interacting polyurethane, comprising the following raw materials in the following weight ratios: 50-200 parts of polydiol, 100-400 parts of diisocyanate, 10-200 parts of flexible hydrazide chain extender, 10-200 parts of rigid chain extender, 1-20 parts of catalyst, and 200-500 parts of anhydrous organic solvent. The polydiol includes polydiol A and polydiol B, each of which is independently selected from polyester diol or polyether diol, and the polydiol A and polydiol B have different chemical structures. The rigid chain extender is 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA).

[0007] More preferably, the weight ratio of polydiol A to polydiol B is 0.25 to 4:1.

[0008] More preferably, the polydiol A and polydiol B are each independently selected from any one of polytetrahydrofuran (PTMEG), polycaprolactone diol (PCL), polyethylene glycol (PEG), or polybutylene adipate (PBA), and the polydiol A and polydiol B have different chemical structures.

[0009] More preferably, the number average molecular weight of each polydiol (NUMBER) M n All are 1000~3000 g·mol -1 .

[0010] More preferably, the number-average molecular weight of the polydiol is 2000 g·mol⁻¹. -1 .

[0011] More preferably, the diisocyanate is either 4,4'-diisocyanate dicyclohexylmethane (HMDI) or diphenylmethane diisocyanate (MDI).

[0012] More preferably, the flexible hydrazide chain extender is any one of carbamate (CHZ), adipic acid dihydrazide (ADH), sebamate (SDH), or dodecanedicarboxylic acid dihydrazide (DDH).

[0013] More preferably, the catalyst is dibutyltin dilaurate (DBTDL).

[0014] More preferably, the anhydrous organic solvent is either anhydrous N,N-dimethylacetamide (DMAc) or anhydrous N,N-dimethylformamide (DMF), and the amount added is sufficient to reduce the viscosity of the system appropriately.

[0015] Preferably, the general structural formula of the supramolecularly interacting polyurethane is as follows: ; Where X and X' are each independently selected , , , Any one of the following, where n is 8 to 45, and X and X' are not the same; Y is or Any one of them; Z is , , , Any one of them; a is 1 ~ 50, b is 1 ~ 30.

[0016] In this invention, the supramolecularly interacting polyurethane comprises polydiol segments X and X', which together constitute a mixed soft segment; the supramolecularly interacting polyurethane uses diisocyanate Y as a hard segment backbone, and the hard segment backbone is interleaved with flexible chain extender hydrazide Z and rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole.

[0017] In this invention, the supramolecularly interacting polyurethane simulates the brick-and-tile layered structure of natural nacre at the molecular level, achieving precise construction of a rigid phase and a flexible interface. Using diisocyanate Y as the hard segment backbone, a highly dynamic flexible chain extender, hydrazide Z, and a chain extender with asymmetric dynamic bond characteristics and a high-rigidity geometric center, 2-(4-aminophenyl)-5-aminobenzimidazole (APBIA), are innovatively interleaved and combined with polyester / ether glycol X and polyester / ether glycol X' mixed soft segments. Through the synergistic effect of constructing mismatched supramolecular interactions and a mixed soft segment system, multiple functional segments are cleverly integrated to construct the supramolecularly interacting polyurethane.

[0018] The second objective of this invention is to provide a method for preparing the supramolecularly interacting polyurethane, comprising the following steps: S1: The diisocyanate solution is added dropwise to the dried and dehydrated polydiol A and polydiol B, and a catalyst is added to carry out the prepolymerization reaction to obtain -NCO-terminated polyurethane prepolymer (PU). S2: Add the flexible hydrazine chain extender solution dropwise to the polyurethane prepolymer to carry out a flexible chain extension reaction and obtain a flexible chain extended product; S3: Mix the rigid chain extender solution with the flexible chain extender product to carry out a rigid chain extension reaction. After the reaction is completed, remove the solvent to obtain the supramolecular interactive polyurethane.

[0019] Preferably, in step S1, the diisocyanate solution is obtained by mixing diisocyanate with anhydrous organic solvent.

[0020] More preferably, in step S1, the amount of anhydrous organic solvent added to the diisocyanate solution is sufficient to reduce the viscosity of the system appropriately.

[0021] Preferably, in step S1, polydiol A and polydiol B are vacuum dried and dehydrated by stirring at 90~130°C for 20~90 minutes, with a stirring speed of 200~1000 rpm.

[0022] Preferably, in step S1, the temperature of the prepolymerization reaction is 50~85°C and the time is 1~6 h.

[0023] Preferably, in step S1, the diisocyanate solution is added dropwise to the dried and dehydrated polydiol A and polydiol B at a rate of 0.2 to 3 mL / min.

[0024] Preferably, in step S2, the flexible hydrazide chain extender solution is obtained by mixing the flexible hydrazide chain extender with an anhydrous organic solvent.

[0025] More preferably, in step S2, the amount of anhydrous organic solvent added to the flexible hydrazide chain extender solution is sufficient to reduce the viscosity of the system appropriately.

[0026] Preferably, in step S2, the reaction temperature of the flexible chain extension reaction is 25~50°C and the time is 3~24 h.

[0027] Preferably, in step S2, the flexible hydrazide chain extender solution is added dropwise to the polyurethane prepolymer at a rate of 0.2 to 3 mL / min.

[0028] Preferably, in step S3, the rigid chain extender solution is obtained by mixing 2-(4-aminophenyl)-5-aminobenzimidazole with anhydrous organic solvent.

[0029] More preferably, in step S3, the amount of anhydrous organic solvent added to the rigid chain extender solution is sufficient to reduce the viscosity of the system appropriately.

[0030] Preferably, in step S3, the reaction temperature of the rigid chain extension reaction is 50~80°C, and the reaction time is 3~24 h.

[0031] Preferably, steps S1-S3 are all performed under a nitrogen protective atmosphere.

[0032] Preferably, steps S1-S3 are all performed under stirring conditions, and the stirring speed is 200~1000 rpm.

[0033] More preferably, in steps S1-S3, the total weight of the anhydrous organic solvent used is 200-500 parts.

[0034] More preferably, the preparation method of the supramolecularly interacting polyurethane specifically includes the following steps: (1) Before use, place the polydiol in a three-necked flask equipped with a thermometer, mechanical stirrer and N2 protection device, and vacuum dry it in an oil bath at 90~130 °C to remove water. Then keep it warm and stir for 20~90 min, and slowly cool the system to 50~85 °C. (2) Add an anhydrous organic solvent to the diisocyanate to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce the catalyst into the three-necked flask of step (2), stir thoroughly at 50~85 °C for 1~6 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 25~50 °C. (4) Add anhydrous organic solvent to the flexible hydrazide chain extender, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 25~50 °C for 3~24 h, and then slowly heat the reaction system to 50~80 °C. (5) Dissolve the rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in an anhydrous organic solvent, and then add it to step (4) to continue the reaction for 3~24 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, thus obtaining the final product supramolecular interaction polyurethane.

[0035] Preferably, the synthetic route of the supramolecularly interacting polyurethane is as follows: .

[0036] The third objective of this invention is to provide an application of the polyurethane-based solid ion-conductive elastomer described above in a software driver.

[0037] Preferably, the soft actuator includes a pneumatic soft gripper, a biomimetic inchworm crawling robot, and an exogenous active powered skeleton.

[0038] More preferably, the supramolecularly interacting polyurethane is used in the pneumatic soft gripper. Thanks to its high bending reliability, strain tolerance and rapid shape recovery capability, the gripper can maintain a stable gripping force output during the periodic pneumatic inflation and deflation process, and can quickly return to its initial shape after the air pressure is removed, thus working stably in gripping scenarios of objects with different shapes.

[0039] More preferably, the supramolecularly interacting polyurethane is used in a biomimetic inchworm crawling robot. Utilizing its anisotropic deformation capability and low stress relaxation characteristics under cyclic loading, the robot can achieve continuous and directional periodic crawling motion under pneumatic drive, exhibiting good motion durability and gait stability.

[0040] More preferably, the supramolecularly interacting polyurethane is used in exogenous active dynamic bone. Based on its suitable flexibility modulus and good biomechanical compatibility, it can assist patients in performing passive joint movements and muscle tension recovery training of the hands, achieving a safe, comfortable and well-compliant rehabilitation training experience.

[0041] The fourth objective of this invention is to provide a polyurethane-based solid ion-conductive elastomer, comprising the following raw materials in the following weight ratios: 100 parts of supramolecularly interacting polyurethane, 10-150 parts of lithium salt, and 150-250 parts of anhydrous organic solvent, wherein the polyurethane is the supramolecularly interacting polyurethane described above.

[0042] Preferably, the lithium salt is any one of lithium bis(trifluoromethanesulfonylimide) (LiTFSI), lithium perchlorate (LiClO4), or lithium dioxalatoborate (LiBOB).

[0043] Preferably, the anhydrous organic solvent is any one of anhydrous N,N-dimethylacetamide or anhydrous N,N-dimethylformamide, and the amount added is sufficient to reduce the viscosity of the system appropriately.

[0044] Preferably, the polyurethane-based solid ion-conductive elastomer is obtained by the coordination reaction of supramolecularly interacting polyurethane with lithium ions.

[0045] The fifth objective of this invention is to provide a method for preparing the polyurethane-based solid ion-conductive elastomer described above. The method involves mixing lithium salt, supramolecularly interacting polyurethane, and anhydrous organic solvent according to a specified ratio, stirring the mixture at 40-80 °C for 8 h to obtain a transparent, viscous solution, and then heating it at 65-95 °C to remove the solvent and solidify it, thereby obtaining the polyurethane-based solid ion-conductive elastomer.

[0046] More preferably, the stirring speed is 200~1000 rpm.

[0047] More preferably, the transparent viscous solution is poured into a glass petri dish and placed on a heating plate at 90 °C to remove the solvent and solidify to form a thin film of polyurethane-based solid ion-conductive elastomer.

[0048] More preferably, the preparation method of the polyurethane-based solid ion-conducting elastomer specifically includes the following steps: 50–150 parts of anhydrous organic solvent were added to the lithium salt to reduce the viscosity of the system and dilute it thoroughly. Then, the solution was added to a pre-prepared supramolecular interaction polyurethane solution. The polymer system was stirred thoroughly at 40–80 °C for 8 h to obtain a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90 °C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable solid-state ion-conductive elastomer.

[0049] The sixth objective of this invention is to provide an application of the polyurethane-based solid ion-conductive elastomer described above in flexible wearable electronic devices.

[0050] Preferably, the flexible wearable electronic device includes a flexible epidermal bioelectrode and a resistive sensor.

[0051] More preferably, the polyurethane-based solid ion-conductive elastomer is used for flexible epidermal bioelectrodes. Based on its excellent bioinertness, high conductivity and conformal adhesion, the electrode can provide low contact impedance for capturing electrocardiogram (ECG) and electromyography (sEMG) signals. It can also be combined with an ECG health monitoring and electromyography feedback control platform to realize physiological signal monitoring and human-computer interaction.

[0052] More preferably, the polyurethane-based solid ion-conductive elastomer is used in flexible resistive sensor devices. Based on its stable ion-conductive network and the linear correlation between deformation-resistance response, it can achieve sensitive detection of external stimuli (such as pressure or strain) and maintain the repeatability of the resistance signal during cyclic loading.

[0053] More preferably, the polyurethane-based solid ion-conductive elastomer is used in a finger array sensor. Utilizing its high sensitivity and differentiated response characteristics to resistance changes at different bending angles, it can accurately respond to and track the movement trajectory of each finger joint, thereby achieving high-fidelity signal acquisition of hand gestures.

[0054] More preferably, the supramolecularly interacting polyurethane and the polyurethane-based solid ion-conducting elastomer can be synergistically applied to flexible wearable rehabilitation electronic devices to jointly construct a solid-state, fully soft digital medical exoskeleton platform, forming an integrated finger rehabilitation system that combines active training and sensing monitoring. The supramolecularly interacting polyurethane possesses excellent flexibility and aerodynamic response properties, enabling the construction of soft pneumatic actuators as active power structures to assist patients in completing finger joint flexion and extension movements, thus aiding in the rehabilitation of hand muscles and joint functions. The polyurethane-based solid ion-conducting elastomer exhibits good deformation-resistance response characteristics, allowing it to be fabricated into flexible resistive sensors that accurately capture finger bending deformation signals, achieving real-time sensing and interactive feedback of hand movements.

[0055] More preferably, the polyurethane-based solid ion-conductive elastomer is used for finger sensory feedback during training and recovery. Based on its ultrasensitive response to micro-strain and the finger movement recognition of resistance change signals, the conductive elastomer can output highly recognizable resistance change signal imprints with individualized characteristics. On this basis, an end-to-end digital intelligent assisted nursing interaction system is comprehensively constructed, connecting physiological micro-strain, AI high-speed decoding, and digital clinical response, to achieve closed-loop intelligent interaction from physiological signals to clinical instructions.

[0056] This invention provides a supramolecularly interacting polyurethane, a polyurethane-based solid ion-conductive elastomer, its preparation method, and its applications. The core technical concept lies in relying on the supramolecular mismatch effect, combined with precise control of molecular chain structure and stepwise chain extension process design, to achieve synergistic optimization of the microstructure and macroscopic properties of the polyurethane system.

[0057] This invention employs a hybrid soft-segment system to maintain the material's highly amorphous state and chain segment mobility, thereby promoting efficient lithium-ion migration. Furthermore, flexible and rigid chain extenders are mismatched within the hard-segment structure, and a dynamic supramolecular crosslinking network combining rigid hydrogen bonds, π-π stacking, and flexible multiple hydrogen bonds is constructed through a stepwise rigid and flexible segmented chain extension process. Relying on the synergistic effect of the rigid-flexible structure, the polyurethane matrix is ​​endowed with excellent toughness, elastic resilience, and damage resistance at the molecular level.

[0058] Rigid hydrogen bonds originate from the high-energy hydrogen bonds formed between the benzimidazole and amide groups in the rigid chain extender APBIA molecule and the polyurethane segments. These rigid hydrogen bonds have high bond energy and strong directionality, forming a dense and difficult-to-dissociate physically cross-linked hard core in the matrix, endowing the material with superior Young's modulus, tensile strength, and fatigue damage resistance. Flexible multiple hydrogen bonds mainly originate from the low-energy, dynamically reversible hydrogen bonds formed between the flexible hydrazine chain extender, the ends of the mixed soft segments, and the polyurethane urethane groups. These hydrogen bond sites are located in a flexible aliphatic chain environment with high conformational freedom, low steric hindrance, and extremely strong dynamic reversibility, enabling stress dissipation and structural self-repair functions.

[0059] Based on this, the unique fused ring and benzene ring conjugated structure of APBIA molecules can form stable intermolecular π-π stacking interactions, inducing supramolecular mismatches in the system in terms of steric hindrance, geometric configuration and hydrogen bond spacing, precisely controlling the hard segment aggregation behavior, and promoting the formation of a uniformly dispersed nanoscale microphase separation microstructure.

[0060] Stepwise chain extension promotes a spatial gradient or alternating arrangement of rigid cross-linked microregions and flexible hydrogen-bonded microregions. This mismatch effectively blocks the excessive crystallization of hard segments, inducing the system to form a uniformly dispersed, extremely small nanoscale microphase separation structure. In experiments, this operation makes the experimental process more controllable.

[0061] Based on this rigid-flexible balanced supramolecular network structure, combined with lithium salt complexation coordination, a stable and efficient ion transport channel is constructed, and the coordination between polymer and lithium ions is optimized. Finally, supramolecular polyurethane and polyurethane-based solid ion-conductive elastomers with excellent comprehensive mechanical properties, stable electromechanical response characteristics and ultra-low strain detection limit are prepared, which fundamentally overcomes the technical drawbacks of traditional polyurethane materials with single structure and prominent performance shortcomings.

[0062] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention simulates the rigid-flexible structural characteristics of the nacreous layer of seashells. By introducing rigid and flexible chain extenders into the system in an alternating manner, a significant supramolecular mismatch effect is formed in terms of spatial geometry, steric hindrance, and hydrogen bond pairing distance, inducing the formation of a highly dispersed nanoscale microphase separation structure in the hard segment phase of polyurethane. Among them, the rigid chain extender contains a double benzene ring structure. Relying on the benzimidazole fused ring and independent benzene ring in the APBIA molecule to construct an extended delocalized π-electron conjugated system, it can achieve strong intermolecular π-π stacking interaction and form a synergistic effect with the rigid hydrogen bonds to jointly stabilize the material skeleton structure.

[0063] (2) The dynamic mismatched supramolecular network constructed in this invention possesses a unique hierarchical energy dissipation mechanism. During the material's deformation under stress, low-bond-energy flexible multiple hydrogen bonds can preferentially break as sacrificial bonds to dissipate energy, while high-bond-energy rigid hydrogen bonds and π-π stacking interactions simultaneously maintain the integrity of the skeleton and transfer the load, effectively releasing internal stress and inhibiting permanent slippage of molecular chains, thus significantly improving the material's strength, toughness, and energy dissipation efficiency. Based on this mechanism, the supramolecularly interacting polyurethane and solid ion-conducting elastomer prepared in this invention possess ultra-high ductility, mechanical strength, and toughness. The ductility can reach 1335.46% and 1839.63%, respectively; the mechanical strength can reach 62.24 MPa and 12.02 MPa, respectively; and the toughness can reach 302.24 MJ·m. -3 54.35 MJ·m -3 This achieves the optimal balance between strength and toughness in mechanical properties.

[0064] (3) Based on the rigid-flexible balance supramolecular cross-linked network structure, this invention constructs a coordinated coordination effect between the mixed soft segments and lithium ions. On the one hand, it can maintain the highly amorphous structure of the polymer, eliminate ion transport barriers, and significantly improve lithium ion migration efficiency; on the other hand, it locks the active supramolecular sites in the system through strong Li-polymer coordination, forming a quasi-covalent topological locking structure. While ensuring ion transport efficiency, it significantly enhances the electromechanical coupling response capability of the material, endowing the conductive elastomer with excellent dynamic sensing performance.

[0065] (4) Benefiting from the dynamic mismatched supramolecular network formed by the interweaving of rigid and flexible chain extenders and the high-strength Li-polymer coordination centers, the material of this invention has excellent air aging resistance, moisture resistance, hydrophobicity and chemical stability. At the same time, the material has excellent puncture resistance and can maintain structural integrity and not fail as a whole under local puncture conditions, making it suitable for complex and ever-changing actual service environments.

[0066] (5) The supramolecular dynamic network constructed in this invention endows the material with excellent self-healing properties, enabling autonomous repair of damaged sites and extending the service life of the material. At the same time, based on the APBIA molecule, the material has a unique intrinsic blue fluorescence visual recognition effect, which enables the visual recognition of material damage and deformation state, enriching the functional properties of the material.

[0067] (6) Based on the advantages of low stress relaxation and resistance to deformation fatigue brought about by the dynamic mismatched supramolecular network, the polyurethane-based solid ion-conductive elastomer of the present invention has excellent comprehensive sensing performance, with an electrical conductivity of up to 1.42 × 10⁻⁶. -2 S·m -1 It can achieve precise detection of minute strain as low as 0.01%, with fast response speed and strong signal stability. When applied to ECG and EMG physiological signal monitoring, it can perform fine decoupling and high-fidelity extraction of weak and complex pathological signals. The signal-to-noise ratio of EMG testing can reach 22.50 dB, which is significantly better than commercial electrodes (18.94 dB). It has strong anti-interference ability and can accurately capture weak motion potentials, ensuring the accuracy and reliability of physiological monitoring data.

[0068] (7) The supramolecular interaction polyurethane and solid ion-conductive elastomer of the present invention have excellent biocompatibility, high cell survival rate, no biotoxicity, and excellent biosafety performance. They can be stably applied to human body-fitting flexible wearable electronic devices and smart medical devices for a long time.

[0069] (8) The two functional materials of this invention can be adapted and synergistically applied to two major scenarios: a solid-state fully soft digital medical exoskeleton rehabilitation platform and an intelligent assisted nursing interaction system. Among them, supramolecular interaction polyurethane can be used to construct a soft pneumatic actuator, which serves as an exogenous active power skeleton to assist patients in completing finger joint flexion and extension movements, effectively realizing rehabilitation training for hand muscle tension regulation and joint movement function; polyurethane-based solid ion-conductive elastomer can accurately capture minute deformations of the fingers and output highly recognizable individualized resistance characteristic signals to complete accurate perception and signal acquisition of hand movement status. Based on this, relying on the excellent deformation-resistance response characteristics of the materials, an end-to-end intelligent nursing interaction system of physiological micro-strain-AI high-speed decoding-digital clinical response can be built. Through the SVM machine learning algorithm, the hand gesture sensing signal is analyzed at high speed and intelligently, and the prediction accuracy of unknown gestures can reach 93.8%, which can accurately convert hand deformation signals into standardized clinical care instructions. Relying on the differentiated functional advantages of the two types of materials, this invention integrates hand rehabilitation training, real-time acquisition of movement information and intelligent clinical interaction, significantly shortening the medical response time and achieving efficient optimization of medical resources. Attached Figure Description

[0070] Figure 1 The synthetic molecular formula of the supramolecularly interacting polyurethane prepared in Example 1 is shown below. Figure 2 The X-ray diffraction (XRD) spectrum (a) and small-angle X-ray scattering (1D SAXS) curve (b) of the supramolecularly interacting polyurethane prepared in Example 1 are shown in the inset (b), which is a 2D SAXS image. Figure 3 Typical stress-strain curves of supramolecularly interacting polyurethane (a) and polyurethane-based solid ion-conducting elastomer (b) prepared in Example 1 are shown. Figure 4 The cyclic tensile curves of the supramolecularly interacting polyurethane and the polyurethane-based solid ion-conducting elastomer prepared in Example 1 under different strains are shown in (a): supramolecularly interacting polyurethane; (b): polyurethane-based solid ion-conducting elastomer and cyclic hysteresis loss and hysteresis ratio (c): supramolecularly interacting polyurethane; (d): polyurethane-based solid ion-conducting elastomer). Figure 5 The single-sided notch tear tensile curves of the supramolecularly interacting polyurethane (a) and the polyurethane-based solid ion-conducting elastomer (b) prepared in Example 1 are shown. Figure 6 Force-displacement curves of the supramolecularly interacting polyurethane (a) and polyurethane-based solid ion-conducting elastomer (b) prepared in Example 1 during puncture resistance testing; Figure 7 The images show the water contact angle test results (a) and typical stress-strain curves (b) of the supramolecularly interacting polyurethane and polyurethane-based solid ion-conductive elastomer prepared in Example 1 before and after 180 days of storage. Figure 8 Thermogravimetric analysis of supramolecularly interacting polyurethane and polyurethane-based solid ion-conducting elastomer prepared in Example 1; Figure 9 Fluorescent images of supramolecularly interacting polyurethane and polyurethane-based solid ion-conducting elastomers prepared in Example 1; Figure 10 Images showing the self-healing microcrack patterns of the polyurethane-based solid ion-conductive elastomer prepared in Example 1; Figure 11 The images show fluorescent live / dead cell staining micrographs (a) and cell viability (b) of the supramolecularly interacting polyurethane and polyurethane-based solid ion-conducting elastomer prepared in Example 1. Figure 12 The attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectra of the supramolecularly interacting polyurethanes prepared in Comparative Example 1 and Example 1 are shown in (a), along with the C═O peaks in the 1600-1750 cm⁻¹ range. -1 Fitting results at (b), (c)); Figure 13 Dynamic thermomechanical analysis (DMA) tests were conducted on the elastomers of supramolecularly interacting polyurethanes prepared in Comparative Example 1 and Example 1 with respect to the loss angle. Figure 14 Molecular dynamics simulation (a) and number of hydrogen bonds in the cohesive energy density system of the supramolecularly interacting polyurethanes prepared in Comparative Examples 2, 3 and 1 are shown in Figure 1. Figure 15 Typical stress-strain curves of supramolecularly interacting polyurethanes prepared in Comparative Examples 2, 3 and 1 are shown. Figure 16 The electrocardiogram (ECG) ((a), (b)) and electromyography (EMG) signals (c) of the polyurethane-based solid ion-conductive elastomer prepared in Example 1 were compared with those of commercial electrodes. Figure 17 The graph shows the response of the relative resistance change rate of the polyurethane-based solid ion-conductive elastomer prepared in Example 1 as a resistive sensor with respect to different strain cycles (a) and loading-unloading frequencies (b). Figure 18 The response time and recovery time of the polyurethane-based solid ion-conducting elastomer prepared in Example 1 were measured by rapid stretching and release of the material. Figure 19 The resistance changes (a) and relative resistance changes (b) of the polyurethane-based solid ion-conductive elastomer prepared in Example 1 during the cut-and-heal cycle. Figure 20 The fabrication process (a) and bending image (b) of the supramolecularly interacting polyurethane prepared in Example 1 applied to the pneumatic actuator; Figure 21 Photographs showing the recovery behavior (i) and gripping behavior (ii) of the supramolecularly interacting polyurethane prepared in Example 1 applied to a pneumatic soft gripper; Figure 22 The images (a) and (b) show the crawling behavior of the supramolecularly interacting polyurethane prepared in Example 1 applied to the biomimetic inchworm crawling robot. Figure 23 The supramolecularly interacting polyurethane prepared in Example 1 was applied to rehabilitation training for passive joint movement and muscle tension recovery assisted by pneumatic actuators. Figure 24 The polyurethane-based solid ion-conductive elastomer prepared in Example 1 was used to sense the signal emitted by the finger in contact, where (a) is the statistical data of the five fingers' signals within the effective time, and (b) to (f) are the extracted signal features of each finger. Figure 25The diagram shows the architecture of four core modules for the overall application of the supramolecularly interacting polyurethane and polyurethane-based solid ion-conducting elastomer prepared in Example 1 in an intelligent assisted nursing interaction system (Ⅰ: sensing mechanism and signal fingerprint curve; Ⅱ: signal extraction and demand conversion system; Ⅲ: clinical application demonstration; Ⅳ: nurse station and clinical response). Figure 26 The supramolecularly interacting polyurethane and polyurethane-based solid ion-conducting elastomer prepared in Example 1 are applied to the demand feedback of a responsive clinical cloud webpage interaction and central monitoring platform. Figure 27 The supramolecularly interacting polyurethane and polyurethane-based solid ion-conductive elastomer prepared in Example 1 were applied to a responsive clinical cloud network interaction and central monitoring platform to accurately identify unknown gestures. Detailed Implementation

[0071] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.

[0072] Unless otherwise specified, the reagents, methods, instruments, and equipment used in this invention are conventional in the art. Unless otherwise specified, the reagents and materials used in the following examples are all commercially available.

[0073] In the following embodiments, S-PU refers to supramolecularly interacting polyurethane, and S-PU-Li refers to polyurethane-based solid ion-conducting elastomer. It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0074] The number-average molecular weight of the polydiols used in the following examples is 2000 g·mol⁻¹. -1 .

[0075] Example 1 The preparation method of the supramolecularly interacting polyurethane of the present invention (named S-PU-1) is as follows: The required raw materials, in parts by weight, are: 75 parts polytetrahydrofuran and 25 parts polyethylene glycol, 220 parts dicyclohexylmethane 4,4'-diisocyanate, 80 parts flexible chain extender adipic acid dihydrazide, 40 parts rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 4 parts catalyst dibutyltin dilaurate, and 200 parts anhydrous N,N-dimethylacetamide. The preparation process is as follows: (1) Place 75 parts of polytetrahydrofuran and 25 parts of polyethylene glycol in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 130 °C and stir for 60 min. Then slowly cool the system to 85 °C. (2) Add 40 parts of anhydrous N,N-dimethylacetamide organic solvent to 220 parts of 4,4'-diisocyanate dicyclohexylmethane to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 4 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 85 °C for 4 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 45 °C. (4) Add 80 parts of anhydrous N,N-dimethylacetamide organic solvent to 80 parts of flexible chain extender adipic acid dihydrazide, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 45 °C for 24 h, and then slowly heat the reaction system to 60 °C. (5) Dissolve 40 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 80 parts of anhydrous N,N-dimethylacetamide organic solvent, and then add it to step (4) to continue the reaction for 24 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-1) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 120 parts lithium bis(trifluoromethanesulfonylimide), and 220 parts anhydrous N,N-dimethylacetamide.

[0076] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylacetamide solvent and set aside. Separately, 120 parts of lithium bis(trifluoromethanesulfonyl)imide were diluted with 120 parts of anhydrous N,N-dimethylacetamide solvent to reduce viscosity. Then, the resulting lithium salt solution was added to the polyurethane solution, and the mixture was stirred thoroughly at 60 °C for 8 h, finally yielding a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90 °C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0077] Test Form The mechanical property testing method for supramolecularly interacting polyurethanes and polyurethane-based solid ion-conducting elastomers of the present invention is as follows: All mechanical testing methods were performed using a universal testing machine at room temperature.

[0078] (1) Cut the test sample into dumbbell-shaped strips and fix them at both ends of the tension clamp. The initial clamping distance is set to 12 mm and the tensioning rate is 50 mm·min. -1 Stress (σ) and elongation at break (ε) are calculated according to Equations 1 and 2: (Equation 1) (Equation 2) In the formula: σ: Tensile strength (MPa); F: The maximum tensile force (N) that the film can withstand when it breaks; b: Width of the film (mm); d: Film thickness (mm); ε: Elongation at break of the composite film (%); L max : Distance between clamps (mm) when the film breaks; L0: The initial distance between the clamps (mm) at the start of the composite film application; (2) In the cyclic tensile test, the cyclic tensile strain of the sample was gradually increased from 100% to 700%, and the loading-unloading process was carried out at a rate of 50 mm·min throughout. -1 The strain rate is determined. Hysteresis energy loss and hysteresis ratio are calculated according to equations 3 and 4: (Equation 3) (Equation 4) In the formula: S s It is the area (MJ·m) between the stretching loading curve and the X-axis boundary. -3 ); S r It is the area of ​​the unloading curve and the X-axis boundary (MJ·m -3 ); (3) Tensile fracture tests were conducted using a single-sided notch, with a crack length of 1 mm. Both notched and unnotched specimens were tested at a crack length of 3 mm·min. -1 The tensile rate was tested. Fracture energy (G) c Calculate according to formula 5: (Equation 5) in λ c This indicates the elongation at tensile fracture of a notched sample.c The notch width is 1.0 mm. w This indicates that the unnotched sample was stretched to... ε c The strain energy calculated from the stress-strain curve at the stress-strain point ( ε c = λ c -1).

[0079] The conductivity testing method for the polyurethane-based solid ion-conducting elastomer of the present invention is as follows: The deformation of the elastic body is precisely controlled by a stepper motor, and the corresponding resistance signal is recorded simultaneously by a digital bridge LCR. The change in relative resistance value is calculated according to Equation 6: (Equation 6) in R 0 and R These represent the initial resistance value and the real-time resistance value under a specific strain, respectively.

[0080] The biocompatibility testing method for supramolecularly interacting polyurethanes and solid ion-conducting elastomers of this invention is as follows: The effect of the material on the viability of NIH 3T3 cells was determined using the CCK-8 assay. NIH 3T3 cells (approximately 4 × 10³ cells / well) were seeded in 96-well plates, followed by the addition of 100 μL of DMEM complete medium (Adamas Life) to each well, and cultured for 24 h at 37 °C in a 5% CO₂ atmosphere. The film samples were then immersed in 20 mL of DMEM complete medium for 24 h, sterilized under UV irradiation for 30 min, and subsequently treated with different concentrations of DMEM complete medium (25 wt%, 50 wt%, 75 wt%, and 100 wt%) to treat NIH 3T3 cells. Cells cultured in DMEM complete medium served as a blank control. After co-culturing for 24 h and 48 h, the medium was removed and the cells were washed with PBS, then 100 μL of fresh medium and 10 μL of CCK-8 solution were added, and co-culturing continued for 1–4 h. The relative cell viability was calculated by measuring the absorbance at 450 nm using an enzyme-linked immunosorbent assay (ELISA) reader, and the biocompatibility of the sample was ultimately assessed.

[0081] Results analysis: Figure 1 The synthetic molecular formula of the supramolecularly interacting polyurethane prepared in Example 1 is shown below. Figure 1It is known that the supramolecular interaction polyurethane network uses 4,4'-diisocyanate dicyclohexylmethane as a hard segment backbone, interleaving flexible chain extenders with highly dynamic properties such as adipic acid dihydrazide and chain extenders with asymmetric dynamic bond properties such as 2-(4-aminophenyl)-5-aminobenzimidazole with a high rigidity geometric center, and combines polytetrahydrofuran glycol (PTMEG) and polyethylene glycol (PEG) mixed dual soft segments.

[0082] Figure 2 The XRD spectrum (a) and 1D SAXS curve (b) of the supramolecularly interacting polyurethane prepared in Example 1 are shown, with the inset in (b) being a 2D SAXS image. Figure 2 As shown in (a), the synthesized elastomer matrix exhibits a broad, diffuse amorphous scattering peak at 2θ ≈ 20°, without any sharp Bragg diffraction peaks. This demonstrates that the entire polymer framework remains in a highly amorphous, amorphous structure. Figure 2 As shown in (b), the system exhibits an extremely sharp and intense scattering peak at a low scattering vector q, indicating a highly dispersed, nanoscale microphase separation structure between the hard segment microregions and the soft segment matrix. Furthermore, in the inset, the unstretched state (S-PU-1) displays a uniform isotropic ring scattering mode; however, when an external tensile strain (S-PU-1-Strain) is applied, the isotropic ring transforms into anisotropic elliptical arcs or streaks elongated along the stretching direction. This phenomenon clearly reveals that the hard segment nanoregions undergo significant directional orientation along the stretching direction during the stretching process. This strain-induced hard segment orientation acts as an effective self-reinforcing crosslinking point in the supramolecular network, thereby endowing the elastomer with excellent strain self-reinforcing properties and high mechanical strength and toughness.

[0083] Figure 3 Typical stress-strain curves are shown for the supramolecularly interacting polyurethane (a) and the polyurethane-based solid ion-conductive elastomer (b) prepared in Example 1. Figure 3 It is evident that in the design of the hard segment network of polyurethane elastomers, the interleaved introduction of supramolecular rigid and flexible chain extenders creates a significant supramolecular mismatch effect (MMSI) in terms of spatial geometry, steric hindrance, and hydrogen bond pairing spacing. Furthermore, the synergistic mixing of the soft segment system effectively maintains the highly amorphous state of the material, thereby promoting efficient lithium-ion migration. The resulting supramolecularly interacting polyurethane and solid-state ion-conducting elastomer exhibit superior ductility (S-PU: 1335.46%, S-PU-Li-1: 1839.63%), higher mechanical strength (S-PU: 62.24 MPa, S-PU-Li-1: 12.02 MPa), and good material toughness (302.24 MJ·m). -3 54.35 MJ·m-3 ).

[0084] Figure 4 The cyclic tensile curves ((a): supramolecularly interacting polyurethane; (b): polyurethane-based solid ion-conducting elastomer) and cyclic hysteresis loss and hysteresis ratio ((c): supramolecularly interacting polyurethane; (d): polyurethane-based solid ion-conducting elastomer) of the supramolecularly interacting polyurethane and polyurethane-based solid ion-conducting elastomer prepared in Example 1 are shown. Figure 4 It is evident that both materials exhibit a significant hysteresis loop, indicating efficient mechanical energy conversion and loss during deformation. Furthermore, the corresponding energy loss and hysteresis curves show that in supramolecularly interacting polyurethanes under large deformation of the supramolecular mismatched network, weak physical cross-linking bonds with lower bond energies (such as hydrogen bonds introduced by the flexible segment) undergo efficient dissociation first to sacrificially dissipate energy, subsequently undergoing dynamic reconstruction during unloading. In contrast, the strongly Li-containing solid ion-conducting elastomers in polyurethane-based solid ion-conducting elastomers… + - Polymer coordination locks the originally active supramolecular sites. The introduction of rigid coordination networks greatly restricts the relative slippage of molecular chains and the dissociation-reconstruction cycle of physical bonds, thereby transforming the system from a high-energy-consuming supramolecular network into a relatively locked quasi-covalent topological structure, thus exhibiting a significant reduction in energy consumption.

[0085] Figure 5 The single-sided notched tear tensile test curves are shown for the supramolecularly interacting polyurethane (a) and the polyurethane-based solid ion-conductive elastomer (b) prepared in Example 1. Figure 5 It can be seen that the critical elongation of the supramolecular interaction polyurethane notched sample ( λ c The elongation at break is as high as 12.08, which is very close to that of the unnotched sample, and it has a high elongation at break of 396.85 KJ·m. -2 The ultra-high fracture energy, after lithium salt doping, is reduced due to soft segment hardening and network partial plasticization, resulting in a decrease in overall dissipation energy. However, the critical tensile ratio of the notched sample still reaches an extremely high 9.70, corresponding to a fracture energy of 13.38 KJ·m. -2 Both materials exhibit notch sensitivity.

[0086] Rigid cylindrical needle puncture tests were performed on two types of elastomer films (0.55 mm thick). Figure 6 Force-displacement curves of the supramolecularly interacting polyurethane (a) and polyurethane-based solid ion-conducting elastomer (b) prepared in Example 1 during puncture resistance testing. Figure 6It is known that the maximum puncture load of the film reached approximately 81.239 N and 3.315 N, respectively, with corresponding critical puncture displacements as high as 29.87 mm and 21.20 mm. Both materials exhibited extremely high puncture resistance, ensuring that even if they encounter local punctures or edge wear during assembly and use, they can still maintain a high-strength mechanical barrier function without cracking or failing, demonstrating extremely high safe service performance.

[0087] Figure 7 The figures (a) show the water contact angle of the supramolecularly interacting polyurethane and the polyurethane-based solid ion-conductive elastomer prepared in Example 1, and (b) show typical stress-strain curves before and after 180 days of storage. Figure 7 As can be seen, both materials exhibit significant hydrophobicity in water contact angle tests, demonstrating excellent resistance to air aging and moisture. Furthermore, the dynamically mismatched supramolecular network (MMSI) formed by the interweaving of rigid-flexible chain extenders and the strong Li... + - The polymer coordination center has extremely high environmental stability and mechanical property stability.

[0088] Figure 8 Thermogravimetric analysis (TGA) of the supramolecularly interacting polyurethane and the polyurethane-based solid ion-conductive elastomer prepared in Example 1. Figure 8 It is evident that both materials possess excellent thermal stability and resistance to volatility.

[0089] Figure 9 Fluorescence images of the supramolecularly interacting polyurethane and the polyurethane-based solid ion-conducting elastomer prepared in Example 1. Figure 9 It is known that since the rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole is a typical quenching fluorescent molecule, the material exhibits unique luminescent properties and has excellent optical patterning recognition characteristics.

[0090] Figure 10 Images showing the self-healing microcrack patterns of the polyurethane-based solid ion-conductive elastomer prepared in Example 1. Figure 10 It can be seen that, based on the self-healing properties of molecular chain interdiffusion and multi-level hydrogen bond reconstruction, the fluorescent traces displayed on the etched pattern on the surface of the elastomer film disappear as the microcracks gradually heal.

[0091] Figure 11 The images show fluorescent live / dead cell staining micrographs (a) and cell viability (b) determined by the CCK-8 assay for the supramolecularly interacting polyurethane and polyurethane-based solid ion-conductive elastomer prepared in Example 1. Figure 11 It is evident that both materials constructed from supramolecular mismatched elastomer networks possess excellent biocompatibility, providing a safety guarantee for their application in wearable medical intelligent interactive sensing.

[0092] Comparative Example 1: This comparative example provides a supramolecularly interacting polyurethane (named S-PU-p-1), which differs from Example 1 in that it uses a single soft segment: The required raw materials are formulated in the following proportions by weight: 100 parts of polytetrahydrofuran, 220 parts of 4,4'-diisocyanate dicyclohexylmethane, 80 parts of flexible chain extender adipic acid dihydrazide, 40 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 4 parts of catalyst dibutyltin dilaurate, and 200 parts of anhydrous N,N-dimethylacetamide. The preparation process is as follows: (1) Place 100 parts of polytetrahydrofuran in a three-necked flask equipped with a thermometer, mechanical stirrer and N2 protection device before use. Dry the flask under vacuum in an oil bath at 130 °C and stir for 60 min. Then slowly cool the system to 85 °C. (2) Add 40 parts of anhydrous N,N-dimethylacetamide organic solvent to 220 parts of 4,4'-diisocyanate dicyclohexylmethane to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 4 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 85 °C for 4 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 45 °C. (4) Add 80 parts of anhydrous N,N-dimethylacetamide organic solvent to 80 parts of flexible chain extender adipic acid dihydrazide, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 45 °C for 24 h, and then slowly heat the reaction system to 60 °C. (5) Dissolve 40 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 80 parts of anhydrous N,N-dimethylacetamide organic solvent, and then add it to step (4) to continue the reaction for 24 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained.

[0093] Comparative Example 2: This comparative example provides a supramolecularly interacting polyurethane (named S-PU-p-2), which differs from Example 1 in that it uses a single rigid chain extender: The required raw materials are in the following proportions by weight: 75 parts polytetrahydrofuran and 25 parts polyethylene glycol, 220 parts dicyclohexylmethane 4,4'-diisocyanate, 120 parts rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 4 parts catalyst dibutyltin dilaurate, and 200 parts anhydrous N,N-dimethylacetamide. The preparation process is as follows: (1) Place 75 parts of polytetrahydrofuran and 25 parts of polyethylene glycol in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 130 °C and stir for 60 min. Then slowly cool the system to 85 °C. (2) Add 40 parts of anhydrous N,N-dimethylacetamide organic solvent to 220 parts of 4,4'-diisocyanate dicyclohexylmethane to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 4 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 85 °C for 4 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 45 °C. (4) Dissolve 120 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 160 parts of anhydrous N,N-dimethylacetamide organic solvent. After the mixture is fully dissolved, add it dropwise to the three-necked flask in step (3). React at 60 °C for 24 h. After the reaction is complete, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, thus obtaining the final product supramolecular interaction polyurethane.

[0094] Comparative Example 3: This comparative example provides a supramolecularly interacting polyurethane (named S-PU-p-4), which differs from Example 1 in that it uses a single flexible chain extender: The required raw materials are in the following proportions by weight: 75 parts of polytetrahydrofuran and 25 parts of polyethylene glycol, 220 parts of 4,4'-diisocyanate dicyclohexylmethane, 120 parts of flexible chain extender adipic acid dihydrazide, 4 parts of catalyst dibutyltin dilaurate, and 200 parts of anhydrous N,N-dimethylacetamide. The preparation process is as follows: (1) Place 75 parts of polytetrahydrofuran and 25 parts of polyethylene glycol in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 130 °C and stir for 60 min. Then slowly cool the system to 85 °C. (2) Add 40 parts of anhydrous N,N-dimethylacetamide organic solvent to 220 parts of 4,4'-diisocyanate dicyclohexylmethane to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 4 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 85 °C for 4 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 45 °C. (4) Add 160 parts of anhydrous N,N-dimethylacetamide organic solvent to 120 parts of flexible chain extender adipic acid dihydrazide. After dissolving completely, add it dropwise to the three-necked flask in step (3). React at 45 °C for 24 h. After the reaction is complete, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, thus obtaining the final product supramolecular interaction polyurethane.

[0095] Figure 12 The ATR-FTIR spectra (a) of the supramolecularly interacting polyurethanes prepared in Comparative Example 1 and Example 1, and the C═O peaks in the spectra at 1600-1750 cm⁻¹. -1 The fitting results at (b) and (c) are given. Figure 12 It is known that for S-PU-p-1 without polyethylene glycol, the overall hydrogen bonding ratio of its internal carbonyl groups is as high as 79.62%, indicating that the hard segments have a very strong tendency for hydrogen bond self-assembly, forming very dense physically cross-linked hard microdomains. When polyethylene glycol is introduced (S-PU-1), the carbonyl hydrogen bonding ratio drops significantly to 63.40%. This reduction in hydrogen bonding further confirms that the strongly polar ether oxygen groups of polyethylene glycol competitively capture the -NH- hydrogen bond donors that originally belonged to the hard segments, disrupting the original close packing and self-association structure of the hard segment molecular chains, thereby exacerbating the compatibility and phase mixing between the soft and hard segments.

[0096] Figure 13 DMA testing of the supramolecularly interacting polyurethane elastomers prepared in Comparative Example 1 and Example 1 with respect to the loss angle. Figure 13 It can be seen that S-PU-p-1 exhibits an extremely sharp and symmetrical Tanδ peak, the corresponding peak temperature of which is the glass transition temperature of the soft segment, approximately -68.4℃. This belongs to a typical, undisturbed, high-mobility polytetrahydrofuran phase. With the addition of polyethylene glycol, the Tanδ peak position clearly splits into two peaks, and the entire peak width shows a significant trend of broadening and flattening.

[0097] Figure 14 Molecular dynamics simulation (a) and the number of hydrogen bonds in the cohesive energy density system of the supramolecularly interacting polyurethanes prepared in Comparative Examples 2, 3, and 1 are shown (b). Figure 14 As shown in (a), density functional theory (DFT) was used to calculate the stable configurations and binding energies of three representative supramolecular dimers after geometric optimization (the binding energy of the flexible-flexible chain extender corresponding to Comparative Example 3 is -241.255 kJ·mol⁻¹). -1 The binding energy of the rigid-rigid chain extender corresponding to Comparative Example 2 is -219.261 kJ·mol⁻¹. -1 The binding energy of the flexible-rigid chain extender corresponding to the example is -174.417 kJ·mol⁻¹.-1 In Example 1, the dimer formed by the mispairing of rigid and flexible chain extenders has the lowest binding energy. Under macroscopic external forces such as tensile deformation, this significant energy gradient difference endows the elastomer with a very unique hierarchical dissipation mechanism. Figure 14 The bar chart in (b) visually shows that the number of hydrogen bonds in the chain extender system under the effect of mismatched MMSI increases significantly, reaching a maximum at S-PU-1. The supramolecular mismatch effect does not lead to a loose network structure; on the contrary, it greatly optimizes the intermolecular filling density and polar interactions inside the hard segments by means of spatial complementarity and synergistic arrangement, thereby constructing the most thermodynamically stable cohesive network.

[0098] Figure 15 Typical stress-strain curves for the supramolecularly interacting polyurethanes prepared in Comparative Examples 2, 3, and 1 are shown. Figure 15 It is evident that the rigid / flexible interleaving in Example 1 most effectively releases steric constraints in space, allowing hydrogen bond donors and acceptors that were previously unable to approach each other due to spatial mismatch to pair efficiently and from multiple angles, significantly increasing the active hydrogen bond association density in the network. Therefore, the supramolecularly interacting polyurethane S-PU-1 prepared in Example 1 exhibits the best mechanical responsiveness.

[0099] In the hard-segment systems of Comparative Example 2 (only rigid chain extenders) and Comparative Example 3 (only flexible chain extenders), under tensile stress, the polymer network lacks channels for stress release due to the overly simplistic hydrogen bond network or excessively locked binding energy. This results in inefficient energy dissipation and ultimately catastrophic fracture of the covalent / physical network. In contrast, in the MMSI mismatched network, the flexible multiple hydrogen bonds with lower bonding energy and flexible conformation act as "sacrificial bonds," undergoing reversible fracture and sliding first, dissipating a significant amount of input mechanical energy. Simultaneously, the rigid multiple hydrogen bonds with extremely high binding energy and stable structure, along with the π-π stacking domains, remain intact as a high-strength physical cross-linking framework, effectively transferring and bearing external loads and resisting permanent plastic slip between chain segments. This reversible dissociation-recombination of sacrificial bonds and the synergistic support of the strong hard-segment microregions endow the polyurethane elastomer with exceptional strength, toughness, and energy dissipation efficiency.

[0100] Example 2 The preparation method of the supramolecular interaction polyurethane (named S-PU-2) in this embodiment is as follows: The required raw materials, in parts by weight, are: 75 parts polyethylene glycol and 25 parts polycaprolactone diol, 400 parts diphenylmethane diisocyanate, 200 parts flexible chain extender carbazide, 100 parts rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 18 parts catalyst dibutyltin dilaurate, and 500 parts anhydrous N,N-dimethylformamide. The preparation process is as follows: (1) Place 75 parts of polyethylene glycol and 25 parts of polycaprolactone glycol in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 120 °C and stir for 20 min. Then slowly cool the system to 60 °C. (2) Add 100 parts of anhydrous N,N-dimethylformamide organic solvent to 400 parts of diphenylmethane diisocyanate to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 18 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 60 °C for 6 hours to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 30 °C. (4) Add 200 parts of anhydrous N,N-dimethylformamide organic solvent to 200 parts of flexible chain extender carbazide, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 30 °C for 15 h, and then slowly heat the reaction system to 50 °C. (5) Dissolve 100 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 200 parts of anhydrous N,N-dimethylformamide organic solvent, and then add it to step (4) to continue the reaction for 5 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-2) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 60 parts lithium perchlorate, and 180 parts anhydrous N,N-dimethylformamide.

[0101] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylformamide solvent and set aside. Separately, 60 parts of lithium perchlorate were diluted with 80 parts of anhydrous N,N-dimethylformamide solvent to reduce viscosity. Subsequently, the resulting lithium salt solution was added to the above polyurethane solution, and the mixture was stirred thoroughly at 50 °C for 8 h to obtain a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90 °C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0102] Example 3 The preparation method of the supramolecular interaction polyurethane (named S-PU-3) in this embodiment is as follows: The required raw materials are formulated in the following proportions by weight: 30 parts of polytetrahydrofuran and 20 parts of polyethylene glycol, 100 parts of diphenylmethane diisocyanate, 10 parts of flexible chain extender adipic acid dihydrazide, 40 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 1 part of catalyst dibutyltin dilaurate, and 200 parts of anhydrous N,N-dimethylacetamide. The preparation process is as follows: (1) Place 30 parts of polytetrahydrofuran and 20 parts of polyethylene glycol in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 95 ℃ and stir for 90 min. Then slowly cool the system to 80 ℃. (2) Add 40 parts of anhydrous N,N-dimethylacetamide organic solvent to 100 parts of diphenylmethane diisocyanate to reduce the viscosity of the system, and after sufficient dilution, drop it into the three-necked flask of step (1); (3) Introduce 1 part of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 80 °C for 4 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 45 °C. (4) Add 80 parts of anhydrous N,N-dimethylacetamide organic solvent to 10 parts of flexible chain extender adipic acid dihydrazide, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 45 °C for 10 h, and then slowly heat the reaction system to 70 °C. (5) Dissolve 40 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 80 parts of anhydrous N,N-dimethylacetamide organic solvent, and then add it to step (4) to continue the reaction for 10 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-3) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 80 parts lithium dioxalate borate, and 200 parts anhydrous N,N-dimethylacetamide.

[0103] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylacetamide solvent and set aside. Separately, 80 parts of lithium dioxaborate were diluted with 100 parts of anhydrous N,N-dimethylacetamide solvent to reduce viscosity. Subsequently, the resulting lithium salt solution was added to the above polyurethane solution, and the mixture was stirred thoroughly at 70°C for 8 hours to obtain a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90°C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0104] Example 4 The preparation method of the supramolecular interaction polyurethane (named S-PU-4) in this embodiment is as follows: The required raw materials are formulated in the following proportions by weight: 50 parts of polycaprolactone diol and 25 parts of polybutylene adipate, 180 parts of diphenylmethane diisocyanate, 10 parts of flexible chain extender dodecanedicarboxylic acid dihydrazide, 100 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 3 parts of catalyst dibutyltin dilaurate, and 280 parts of anhydrous N,N-dimethylformamide. The preparation process is as follows: (1) Place 50 parts of polycaprolactone diol and 25 parts of polybutylene adipate in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 120 °C and stir for 45 min. Then slowly cool the system to 70 °C. (2) Add 60 parts of anhydrous N,N-dimethylformamide organic solvent to 180 parts of diphenylmethane diisocyanate to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 3 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 70 °C for 3 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 40 °C. (4) Add 110 parts of anhydrous N,N-dimethylformamide organic solvent to 10 parts of flexible chain extender dodecanedicarboxylic acid dihydrazide, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 40 °C for 20 h, and then slowly heat the reaction system to 75 °C. (5) Dissolve 100 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 100 parts of anhydrous N,N-dimethylformamide organic solvent, and then add it to step (4) to continue the reaction for 5 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-4) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 10 parts lithium bis(trifluoromethanesulfonylimide), and 150 parts anhydrous N,N-dimethylformamide.

[0105] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylformamide solvent and set aside. Separately, 10 parts of lithium bis(trifluoromethanesulfonyl)imide were diluted with 50 parts of anhydrous N,N-dimethylformamide solvent to reduce viscosity. Subsequently, the resulting lithium salt solution was added to the above polyurethane solution, and the mixture was stirred thoroughly at 75 °C for 8 h to obtain a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90 °C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0106] Example 5 The preparation method of the supramolecular interaction polyurethane (named S-PU-5) in this embodiment is as follows: The required raw materials are formulated in the following proportions by weight: 100 parts of polytetrahydrofuran and 25 parts of polycaprolactone diol, 240 parts of 4,4'-diisocyanate dicyclohexylmethane, 60 parts of flexible chain extender carbazide, 50 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 6 parts of catalyst dibutyltin dilaurate, and 300 parts of anhydrous N,N-dimethylformamide. The preparation process is as follows: (1) Place 100 parts of polytetrahydrofuran and 25 parts of polycaprolactone diol in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 100 °C and stir for 80 min. Then slowly cool the system to 85 °C. (2) Add 60 parts of anhydrous N,N-dimethylformamide organic solvent to 240 parts of 4,4'-diisocyanate dicyclohexylmethane to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 6 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 85 °C for 1 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 50 °C. (4) Add 120 parts of anhydrous N,N-dimethylformamide organic solvent to 60 parts of flexible chain extender carbazide, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 50 °C for 3 h, and then slowly heat the reaction system to 80 °C. (5) Dissolve 50 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 120 parts of anhydrous N,N-dimethylformamide organic solvent, and then add it to step (4) to continue the reaction for 20 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-5) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 120 parts lithium perchlorate, and 200 parts anhydrous N,N-dimethylformamide.

[0107] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylformamide solvent and set aside. Separately, 120 parts of lithium perchlorate were diluted with 100 parts of anhydrous N,N-dimethylformamide solvent to reduce viscosity. Then, the resulting lithium salt solution was added to the polyurethane solution, and the mixture was stirred thoroughly at 80 °C for 8 h, finally yielding a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90 °C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0108] Example 6 The preparation method of the supramolecular interaction polyurethane (named S-PU-6) in this embodiment is as follows: The required raw materials, in parts by weight, are: 100 parts polyethylene glycol and 50 parts polybutylene adipate, 360 parts dicyclohexylmethane 4,4'-diisocyanate, 200 parts flexible chain extender sebacate hydrazine, 10 parts rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 16 parts catalyst dibutyltin dilaurate, and 500 parts anhydrous N,N-dimethylacetamide. The preparation process is as follows: (1) Place 100 parts of polyethylene glycol and 50 parts of polybutylene adipate in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 110 °C and stir for 20 min. Then slowly cool the system to 60 °C. (2) Add 100 parts of anhydrous N,N-dimethylacetamide organic solvent to 360 parts of 4,4'-diisocyanate dicyclohexylmethane to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 16 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 60 °C for 4 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 25 °C. (4) Add 200 parts of anhydrous N,N-dimethylacetamide organic solvent to 200 parts of flexible chain extender sebacate hydrazine, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 25 °C for 24 h, and then slowly heat the reaction system to 60 °C. (5) Dissolve 10 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 200 parts of anhydrous N,N-dimethylacetamide organic solvent, and then add it to step (4) to continue the reaction for 3 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-6) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 150 parts lithium dioxalate borate, and 250 parts anhydrous N,N-dimethylacetamide.

[0109] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylacetamide solvent and set aside. Separately, 150 parts of lithium dioxaborate were diluted with 150 parts of anhydrous N,N-dimethylacetamide solvent to reduce viscosity. Subsequently, the resulting lithium salt solution was added to the above polyurethane solution, and the mixture was stirred thoroughly at 60°C for 8 hours to obtain a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90°C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0110] Example 7 The preparation method of the supramolecular interaction polyurethane (named S-PU-7) in this embodiment is as follows: The required raw materials, in parts by weight, are: 75 parts of polycaprolactone diol and 25 parts of polybutylene adipate, 270 parts of 4,4'-diisocyanate dicyclohexylmethane, 10 parts of flexible chain extender carbazide, 200 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 8 parts of catalyst dibutyltin dilaurate, and 250 parts of anhydrous N,N-dimethylformamide. The preparation process is as follows: (1) Place 75 parts of polycaprolactone diol and 25 parts of polybutylene adipate in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in a 90 ℃ oil bath and stir for 45 min. Then slowly cool the system to 65 ℃. (2) Add 50 parts of anhydrous N,N-dimethylformamide organic solvent to 270 parts of 4,4'-diisocyanate dicyclohexylmethane to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 8 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 65 °C for 6 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 30 °C. (4) Add 100 parts of anhydrous N,N-dimethylformamide organic solvent to 10 parts of flexible chain extender carbazide, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 30 °C for 15 h, and then slowly heat the reaction system to 70 °C. (5) Dissolve 200 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 100 parts of anhydrous N,N-dimethylformamide organic solvent, and then add it to step (4) to continue the reaction for 10 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-7) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 150 parts lithium bis(trifluoromethanesulfonylimide), and 220 parts anhydrous N,N-dimethylformamide.

[0111] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylformamide solvent and set aside. Separately, 150 parts of lithium bis(trifluoromethanesulfonyl)imide were diluted with 120 parts of anhydrous N,N-dimethylformamide solvent to reduce viscosity. Subsequently, the resulting lithium salt solution was added to the above polyurethane solution, and the mixture was stirred thoroughly at 80 °C for 8 h to obtain a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90 °C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0112] Example 8 The preparation method of the supramolecular interaction polyurethane (named S-PU-8) in this embodiment is as follows: The required raw materials are formulated in the following proportions by weight: 30 parts of polytetrahydrofuran and 20 parts of polycaprolactone diol, 220 parts of diphenylmethane diisocyanate, 10 parts of flexible chain extender sebacate hydrazine, 160 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 4 parts of catalyst dibutyltin dilaurate, and 200 parts of anhydrous N,N-dimethylformamide. The preparation process is as follows: (1) Place 30 parts of polytetrahydrofuran and 20 parts of polycaprolactone diol in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 100 °C and stir for 50 min. Then slowly cool the system to 70 °C. (2) Add 40 parts of anhydrous N,N-dimethylformamide organic solvent to 220 parts of diphenylmethane diisocyanate to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 4 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 70 °C for 4 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 30 °C. (4) Add 80 parts of anhydrous N,N-dimethylformamide organic solvent to 10 parts of flexible chain extender sebacate hydrazine, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 30 °C for 10 h, and then slowly heat the reaction system to 70 °C. (5) Dissolve 160 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 80 parts of anhydrous N,N-dimethylformamide organic solvent, and then add it to step (4) to continue the reaction for 15 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-8) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 10 parts lithium perchlorate, and 250 parts anhydrous N,N-dimethylformamide.

[0113] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylformamide solvent and set aside. Separately, 10 parts of lithium perchlorate were diluted with 150 parts of anhydrous N,N-dimethylformamide solvent to reduce viscosity. Subsequently, the resulting lithium salt solution was added to the above polyurethane solution, and the mixture was stirred thoroughly at 60 °C for 8 h to obtain a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90 °C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0114] Example 9 The preparation method of the supramolecular interaction polyurethane (named S-PU-9) in this embodiment is as follows: The required raw materials, in parts by weight, are: 60 parts polyethylene glycol and 15 parts polybutylene adipate, 320 parts diphenylmethane diisocyanate, 115 parts flexible chain extender sebacate hydrazine, 130 parts rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 10 parts catalyst dibutyltin dilaurate, and 350 parts anhydrous N,N-dimethylacetamide. The preparation process is as follows: (1) Place 60 parts of polyethylene glycol and 15 parts of polybutylene adipate in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 110 °C and stir for 90 min. Then slowly cool the system to 50 °C. (2) Add 70 parts of anhydrous N,N-dimethylacetamide organic solvent to 320 parts of diphenylmethane diisocyanate to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 10 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 50 °C for 6 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 25 °C. (4) Add 140 parts of anhydrous N,N-dimethylacetamide organic solvent to 115 parts of flexible chain extender sebacate hydrazine, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 25 °C for 24 h, and then slowly heat the reaction system to 50 °C. (5) Dissolve 130 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 140 parts of anhydrous N,N-dimethylacetamide organic solvent, and then add it to step (4) to continue the reaction for 5 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-9) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 120 parts lithium dioxalate borate, and 200 parts anhydrous N,N-dimethylacetamide.

[0115] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylacetamide solvent and set aside. Separately, 120 parts of lithium dioxaborate were diluted with 100 parts of anhydrous N,N-dimethylacetamide solvent to reduce viscosity. Then, the resulting lithium salt solution was added to the polyurethane solution, and the mixture was stirred thoroughly at 40°C for 8 hours, finally yielding a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90°C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0116] Example 10 The preparation method of the supramolecular interaction polyurethane (named S-PU-10) in this embodiment is as follows: The required raw materials are formulated in the following proportions by weight: 150 parts of polytetrahydrofuran and 50 parts of polybutylene adipate, 350 parts of diphenylmethane diisocyanate, 100 parts of flexible chain extender dodecanedicarboxylic acid dihydrazide, 50 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 14 parts of catalyst dibutyltin dilaurate, and 450 parts of anhydrous N,N-dimethylacetamide. The preparation process is as follows: (1) Place 150 parts of polytetrahydrofuran and 50 parts of polybutylene adipate in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 95 °C and stir for 60 min. Then slowly cool the system to 85 °C. (2) Add 90 parts of anhydrous N,N-dimethylacetamide organic solvent to 350 parts of diphenylmethane diisocyanate to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 14 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 85 °C for 3 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 50 °C. (4) Add 180 parts of anhydrous N,N-dimethylacetamide organic solvent to 100 parts of flexible chain extender dodecanedicarboxylic acid dihydrazide, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 50 °C for 3 h, and then slowly heat the reaction system to 80 °C. (5) Dissolve 50 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 180 parts of anhydrous N,N-dimethylacetamide organic solvent, and then add it to step (4) to continue the reaction for 24 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer (named S-PU-Li-10) in this embodiment is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 80 parts lithium bis(trifluoromethanesulfonylimide), and 180 parts anhydrous N,N-dimethylacetamide.

[0117] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylacetamide solvent and set aside. Separately, 80 parts of lithium bis(trifluoromethanesulfonyl)imide were diluted with 80 parts of anhydrous N,N-dimethylacetamide solvent to reduce viscosity. Subsequently, the resulting lithium salt solution was added to the above polyurethane solution, and the mixture was stirred thoroughly at 70 °C for 8 h to obtain a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90 °C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0118] Example 11 The preparation method of the supramolecular interaction polyurethane (named S-PU-11) in this embodiment is as follows: The required raw materials, in parts by weight, are: 100 parts polyethylene glycol and 75 parts polycaprolactone diol, 400 parts dicyclohexylmethane 4,4'-diisocyanate, 200 parts flexible chain extender adipic acid dihydrazide, 35 parts rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 20 parts catalyst dibutyltin dilaurate, and 500 parts anhydrous N,N-dimethylformamide. The preparation process is as follows: (1) Place 100 parts of polyethylene glycol and 75 parts of polycaprolactone glycol in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in an oil bath at 130 °C and stir for 20 min. Then slowly cool the system to 80 °C. (2) Add 100 parts of anhydrous N,N-dimethylformamide organic solvent to 400 parts of 4,4'-diisocyanate dicyclohexylmethane to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 20 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 80 °C for 3 hours to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 45 °C. (4) Add 200 parts of anhydrous N,N-dimethylformamide organic solvent to 200 parts of flexible chain extender adipic acid dihydrazide, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 45 °C for 20 h, and then slowly heat the reaction system to 60 °C. (5) Dissolve 35 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 200 parts of anhydrous N,N-dimethylformamide organic solvent, and then add it to step (4) to continue the reaction for 24 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-11) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 150 parts lithium perchlorate, and 160 parts anhydrous N,N-dimethylformamide.

[0119] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylformamide solvent and set aside. Separately, 150 parts of lithium perchlorate were diluted with 60 parts of anhydrous N,N-dimethylformamide solvent to reduce viscosity. Subsequently, the resulting lithium salt solution was added to the above polyurethane solution, and the mixture was stirred thoroughly at 50 °C for 8 h to obtain a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90 °C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0120] Example 12 The preparation method of the supramolecular interaction polyurethane (named S-PU-12) in this embodiment is as follows: The required raw materials are formulated in the following proportions by weight: 100 parts of polytetrahydrofuran and 75 parts of polybutylene adipate, 380 parts of dicyclohexylmethane 4,4'-diisocyanate, 200 parts of flexible chain extender dodecanedicarboxylic acid dihydrazide, 15 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 16 parts of catalyst dibutyltin dilaurate, and 470 parts of anhydrous N,N-dimethylacetamide. The preparation process is as follows: (1) Place 100 parts of polytetrahydrofuran and 75 parts of polybutylene adipate in a three-necked flask equipped with a thermometer, a mechanical stirrer and a N2 protection device before use. Dry the flask under vacuum in a 90 ℃ oil bath to remove water and keep it warm and stirred for 90 min. Then slowly cool the system to 60 ℃. (2) Add 94 parts of anhydrous N,N-dimethylacetamide organic solvent to 380 parts of 4,4'-diisocyanate dicyclohexylmethane to reduce the viscosity of the system, and after sufficient dilution, add it dropwise to the three-necked flask of step (1); (3) Introduce 16 parts of dibutyltin dilaurate into the three-necked flask of step (2), stir thoroughly at 60 °C for 4 h to generate -NCO-terminated polyurethane prepolymer, and then slowly cool the reaction system to 30 °C. (4) Add 188 parts of anhydrous N,N-dimethylacetamide organic solvent to 200 parts of flexible chain extender adipic acid dihydrazide, dissolve it completely, and then drop it into the three-necked flask of step (3). React at 30 °C for 24 h, and then slowly heat the reaction system to 60 °C. (5) Dissolve 15 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole in 188 parts of anhydrous N,N-dimethylacetamide organic solvent, and then add it to step (4) to continue the reaction for 3 h. After the reaction is completed, pour the mixture into a petri dish and place it on a hot plate to dry and remove the solvent, and the final product supramolecular interaction polyurethane is obtained. The preparation method of the polyurethane-based solid ion-conducting elastomer in this embodiment (named S-PU-Li-12) is as follows: The required raw materials are in the following proportions by weight: 100 parts supramolecular interaction polyurethane, 10 parts lithium dioxalate borate, and 250 parts anhydrous N,N-dimethylacetamide.

[0121] The preparation process is as follows: 100 parts of fully reacted supramolecularly interacting polyurethane were dissolved in 100 parts of anhydrous N,N-dimethylacetamide solvent and set aside. Separately, 10 parts of lithium dioxaborate were diluted with 150 parts of anhydrous N,N-dimethylacetamide solvent to reduce viscosity. Subsequently, the resulting lithium salt solution was added to the above polyurethane solution, and the mixture was stirred thoroughly at 60°C for 8 hours to obtain a homogeneous, transparent, viscous solution. The reactant solution was poured into a glass petri dish and placed on a heated plate at 90°C to remove the solvent and solidify the film, ultimately obtaining a homogeneous and stable polyurethane-based solid ion-conductive elastomer.

[0122] The tensile strength and elongation at break of the supramolecularly interacting polyurethanes described in Examples 1-12 above are shown in Table 1.

[0123] The tensile strength, elongation at break, and conductivity of the polyurethane-based solid ion-conductive elastomers described in Examples 1-12 above are shown in Table 2.

[0124] Table 1. Tensile strength and elongation at break of the supramolecularly interacting polyurethanes described in Examples 1-12 Table 2. Tensile strength, elongation at break, and electrical conductivity of the polyurethane-based ionogels described in Examples 1-12. Application Case 1 Based on the excellent bioinertness of supramolecularly interacting polyurethane and polyurethane-based solid ion-conducting elastomers, highly conductive, conformally attached polyurethane-based solid ion-conducting elastomers are used to prepare flexible epidermal bioelectrodes, providing low contact impedance to capture cardiac and electromyography signals. Combined with an electrocardiogram (ECG) health monitoring and electromyography (sEMG) feedback control platform, the potential for physiological signal monitoring and human-computer interaction can be realized.

[0125] Figure 16 This study compares the electrocardiogram (ECG) and electromyography (EMG) signals detected by the polyurethane-based solid ion-conducting elastomer prepared in Example 1 with those detected by a commercial Ag / AgCl electrode. Figure 16 As shown in (a) and (b), the collected electrocardiogram signals exhibit clear P waves, QRS waves, and T wave pulses. Furthermore, during the ultra-long continuous waveform capture of up to 25 seconds, the output electrocardiogram potential energy curve shows a relatively pure, stable, and highly stable baseline trend without any noise interference, which is comparable to commercial electrodes. Figure 16 In (c), under continuous 50-second periodic muscle contraction-relaxation mechanical loading, the electrode exhibits sensitive electrical signal capture capabilities. Furthermore, the polyurethane-based solid-state ion-conductive elastomer electrode recorded an sEMG signal signal-to-noise ratio (SNR) of 22.5 dB, higher than that of commercial electrodes (18.94 dB), demonstrating high signal quality and strong noise resistance in extracting weak motion potentials. In the normalized dynamic time-frequency energy spectrum output synchronously on the right, the complete energy flow evolution details of the muscle from resting to instantaneous explosive contraction and then to relaxation are accurately captured. Therefore, the flexible ion electrode not only achieves lossless conduction of macroscopic electrical pathways but also possesses high-fidelity detection capabilities for fine decoupling and distortion-free extraction of weak and complex ECG pathological signals.

[0126] Application Case 2 The polyurethane-based solid ion-conductive elastomer prepared in Example 1 was cut into strips and assembled into a resistive sensor by connecting copper wires to both ends. This sensor can detect external stimuli, such as pressure or strain, by detecting changes in the internal resistance of the material. The corresponding resistance signal was recorded using a digital bridge LCR meter.

[0127] Figure 17 This is a test graph showing the relative resistance change rate response of the resistive sensor with respect to different strain cycles (a) and loading-unloading frequencies (b). The unique energy dissipation mechanism of the MMSI structure in the polyurethane-based solid ion-conductive elastomer of this invention endows the material with excellent low-stress relaxation characteristics and resistance to deformation fatigue. Figure 17As shown in (a), as the mechanical strain gradually increases from 0.01% to 150%, a highly reversible and repeatable relative resistance change signal is generated, indicating its high sensitivity and reliability in detecting various strains. Notably, as shown in the inset, this ionic elastomer can detect regular signals down to 0.01% strain, demonstrating excellent ultra-low detection limit capability, meaning it can be used to detect minute deformation movements. Figure 17 (b) shows the loading of 50% strain (50% s) at different tensile rates. -1 Under resistance response testing, the sensor's ΔR / R0 change amplitude remained essentially stable and maintained excellent rate independence, demonstrating good dynamic response stability. This proves the potential application of polyurethane-based solid-state ionic conductive elasticity in electronic sensors.

[0128] Figure 18 The response time and recovery time of the polyurethane-based solid ion-conductive elastomer prepared in Example 1 are measured by rapid stretching and release. Figure 18 It can be seen that the ion-conductive elastomer has an extremely fast response speed (69 ms) and recovery capability (62 ms), which ensures the accuracy and timeliness of the sensor when monitoring high-frequency dynamic signals in real time.

[0129] Figure 19 The resistance changes (a) and relative resistance changes (b) of the polyurethane-based solid ion-conductive elastomer prepared in Example 1 during the cut-and-heal cycle are shown. Figure 19 As shown in (a), when the thin film connected to the circuit is cut, the loop resistance jumps to infinity; when the two cut surfaces re-contact, the resistance achieves continuous permeation and transport of internal particles with an extremely low delay of only 55.4 ms, triggering the healing of the electrical pathway and restoring the loop resistance to the original baseline level. Moreover, in five consecutive cut-and-heal cycle tests, the resistance response of the ion-conductive elastomer shows good repeatability, indicating that the conductive network inside the conductive elastomer can achieve rapid and stable reconstruction. Figure 19 Figure (b) shows that the resistance responses of sensors with different notch sizes are highly similar under the same deformation, demonstrating the material's robustness against notch stress concentration. These performance tests verify that the polyurethane-based solid ion-conductive elastomer of this invention, as a resistive sensor, has high sensitivity and excellent micro-deformation response characteristics, and has potential application prospects in most complex usage environments of human-computer interaction detection and wearable devices.

[0130] Application Case 3 Based on the excellent mechanical flexibility and aerodynamic response characteristics of the supramolecular interaction polyurethane of this invention, a pneumatic soft gripper and a multi-cavity integrated pneumatic crawling robot (bionic inchworm crawling robot) were designed and constructed.

[0131] Figure 20 The supramolecularly interacting polyurethane prepared in Example 1 was used in the fabrication and demonstration of a pneumatic soft gripper. Figure 20 As shown in (a), the soft gripper is manufactured using a process of separate casting followed by bonding and integration, specifically including the following steps: (1) Preparation of the pneumatic body: A mold with a multi-cavity structure is provided, wherein two rows of cavities are symmetrically arranged in the mold; the supramolecular interaction polyurethane in Example 1 is injected into the cavity of the mold, and after curing and molding, the mold is demolded to obtain a pneumatic body with a multi-cavity structure.

[0132] (2) Preparation of strain confinement layer: Take the supramolecularly interacting polyurethane elastomer from Example 1 and prepare it into a thin film as a strain confinement layer.

[0133] (3) Assembly and integration: The pneumatic body obtained in step (1) and the strain limiting layer obtained in step (2) are bonded together with silicone glue, and an air supply duct is introduced into the pneumatic body to obtain the pneumatic soft gripper.

[0134] The core function of the strain-limiting layer is to restrict the elongation of the bottom by utilizing its relatively low tensile deformation capacity, thereby forcing the actuator to bend directionally towards the unrestricted side of the main body during inflation. Its overall actuation behavior relies entirely on the injection and expulsion of internal gas, requiring no rigid frame or additional transmission mechanism. This is achieved thanks to the excellent elastic recovery properties of pure polyurethane and the rationality of its structural design. Figure 20 (b) shows that the pneumatic soft gripper exhibits extremely high bending reliability.

[0135] Depend on Figure 21 It is evident that this pneumatic soft gripper exhibits over 100% strain tolerance and rapid shape recovery capability. Furthermore, this pneumatic soft gripper can grasp a syringe during gas injection and move it through bending deformation during gas-driven operation.

[0136] Figure 22 The images (a) and (b) show a schematic diagram of the crawling motion of the supramolecularly interacting polyurethane prepared in Example 1 applied to a biomimetic inchworm crawling robot. The preparation method of this biomimetic inchworm crawling robot is the same as that of the pneumatic soft gripper described above, except that this biomimetic inchworm crawling robot is formed by three pneumatic bodies with multi-cavity structures connected in series.

[0137] Depend on Figure 22As shown in (a), by implementing alternating air intake and exhaust timing control on the three cavities C1, C2 and C3, the soft robot can be endowed with asymmetric periodic crawling behavior similar to that of inchworms in nature. Figure 22 Figure (b) shows the movement trajectory of the crawling robot in actual testing (from (i) to (vi)). By precisely modulating the aerodynamic timing of the multi-cavity, the soft robot can achieve stable, continuous, and directional crawling motion on a horizontal track, fully demonstrating the great application potential of the supramolecularly interacting polyurethane (pure polyurethane material) of this invention in the fields of flexible intelligent actuation and soft biomimetic robots.

[0138] Application Case 4 To evaluate the performance of supramolecularly interacting polyurethanes and polyurethane-based solid ion-conductive elastomers constructed based on multimorphic supramolecular mismatch interactions (MMSI) in clinical human-computer interaction and intelligent medical care, this invention further develops a closed-loop intelligent rehabilitation and auxiliary communication system that integrates a soft pneumatic robot, a multi-channel strain sensor array, and a support vector machine (SVM) algorithm. This system breaks through the limitations of traditional rigid assistive exoskeletons and single-modal sensing, and realizes cross-modal advanced human-computer interaction with active sensing, intelligent decoding, and precise driving.

[0139] Figure 23 The supramolecularly interacting polyurethane prepared in Example 1 was applied to a pneumatic actuator (similar to the pneumatic soft gripper in Application Case 3) to assist in passive joint movement and muscle tension recovery rehabilitation training. Figure 23 It is known that constructing a flexible adaptive pneumatic actuator as an exogenous active power skeleton can provide a weak response to the residual peripheral nerves in the patient's hand, assisting the patient in joint movement and muscle tension recovery training.

[0140] Figure 24 The polyurethane-based solid ion-conductive elastomer prepared in Example 1 was applied to sense signals emitted by contacting fingers. (a) shows the statistical data of signals from the five fingers within the effective time period, and (b) to (f) show the extracted signal characteristics of each finger. Figure 24 It is known that polyurethane-based solid ion-conductive elastomer films, which possess high tensile strength, high conductivity, and low signal hysteresis, are used to fabricate independent resistive sensors. These sensors are then sequentially attached to the joints of the thumb, index finger, middle finger, ring finger, and little finger, thus forming a multi-channel strain sensing array. This enables independent acquisition and parallel monitoring of the five finger movement signals. When a patient performs a specific bending motion with the assistance of a pneumatic actuator or voluntarily, the supramolecular network within the sensor network undergoes microscopic mismatch and charge transport channel reconstruction under external force, thereby outputting a highly distinctive resistance change signal imprint that is highly recognizable by finger movement.

[0141] A soft pneumatic actuator constructed from supramolecularly interacting polyurethane provides active rehabilitation drive power, while a polyurethane-based solid ion-conductive elastomer constructs a multi-channel strain sensor array to achieve precise perception of hand movements. The two work together to construct a solid-state, fully soft digital medical exoskeleton rehabilitation platform, realizing the integrated function of active finger rehabilitation training and passive perception of motion signals.

[0142] Figure 25 The diagram shows the architecture of the four core modules for the overall application of the supramolecularly interacting polyurethane and polyurethane-based solid ion-conductive elastomer prepared in Example 1 to the intelligent assisted nursing interaction system.

[0143] like Figure 25 As shown, the entire system is divided into four units: sensing mechanism and signal fingerprint, corresponding demand conversion system, clinical application and advantages, and nurse station and clinical response. The five-finger feature signal extraction content corresponding to the sensing mechanism and signal fingerprint module specifically corresponds to the previous text. Figure 24 The signal features extracted from each finger in (b) to (f) are completely consistent in terms of feature curves and numerical results. Thanks to the excellent deformation-resistance response characteristics of the polyurethane-based solid ion-conductive elastomer of this invention, it can convert hand mechanical deformation into an acquireable resistance signal. To achieve efficient and lossless signal conversion from human hand mechanical deformation to clinical care needs, this system builds an end-to-end digital intelligent communication system encompassing physiological micro-strain, AI high-speed decoding, and digital clinical response. By introducing an adaptive machine learning algorithm, it intelligently analyzes and extracts features from the dynamic resistance change waveforms acquired by the sensors, identifying the feature signals corresponding to gestures and converting them into stable and reliable action trigger signals.

[0144] All data computations in this application case were completed in a Python programming environment: the NumPy library was used for preprocessing the sensing impedance signal and performing time-domain feature calculations; a gesture classification and recognition model was built using the Support Vector Machine (SVM) library from the scikit-learn machine learning library; the raw impedance test data stored in an Excel file was read using openpyxl; and the system visualization and local verification interface was implemented as a local web service based on Streamlit. This system uses an existing mature classification model, and this application case only exemplifies one application method of this material.

[0145] The signal processing flow is as follows: First, the acquired five-finger dynamic resistance timing signal is subjected to baseline correction and noise filtering, and the resistance change rate, deformation response time, and signal recovery rate of each finger channel are extracted as feature fingerprints; then, an adaptive threshold algorithm is used to suppress jitter interference and distinguish multi-finger gesture signals; the extracted feature vectors are input into the trained classification model to complete the high-speed AI decoding and accurate recognition of gesture actions; the recognition results output by the model are accurately mapped to the corresponding clinical nursing request instructions, completing the digital clinical response closed loop; finally, the results are displayed through a visual interface, realizing the intelligent and automated conversion from weak physiological deformation signals to standardized clinical care instructions.

[0146] based on Figure 25 The system can recognize typical hand gestures corresponding to the five fingers. The resistance sensing characteristics and mapping clinical needs corresponding to each finger gesture are shown in the following examples: Thumb bending action: When the thumb completes the bending deformation, the resistive sensor based on polyurethane-based solid ion-conductive elastomer film undergoes tensile-compression deformation. The sensor resistance change rate reaches 0.6~0.75. After the characteristic signal is identified and matched by the algorithm, the action trigger signal is output: drinking water. Index finger bending action: When the index finger completes the bending deformation, the sensor resistance change rate reaches 0.45~0.55, and the action trigger signal is output: roll over; Middle finger bending action: When the middle finger completes the bending deformation, the sensor resistance change rate reaches 0.75~0.85, and the action trigger signal is output: pain relief is needed; Ring finger bending action: When the ring finger completes the bending deformation, the sensor resistance change rate reaches 0.35~0.45, and the action trigger signal is output: go to the toilet; Little finger bending action: When the little finger completes the bending deformation, the sensor resistance change rate reaches 0.30~0.35, and the action trigger signal is output: emergency call.

[0147] When the fingers return to a relaxed state, the rate of change of resistance in each channel returns to the initial reference value, completing one complete signal cycle.

[0148] The above resistance change rate range is an exemplary test result and may vary due to factors such as sensor film thickness, assembly process, and pre-stretching conditions. It is only used to characterize the deformation-resistance response behavior of the material of the present invention and does not constitute a limitation on the parameters of the material of the present invention.

[0149] The system decodes the sensor signals of the five gestures mentioned above, directly mapping hand movements to five high-frequency, high-priority clinical care requests in a ward setting. The recognized instructions are simultaneously pushed to the central display screen at the nursing station and to the mobile terminals worn by medical staff. Nurses can use a visual icon interface to read patients' care requests in real time, thereby reducing nursing response delays. This interaction mode does not require patients to speak, and while protecting patient privacy and dignity, it enables dynamic allocation of medical and nursing resources, making it suitable for bedridden patients with aphasia, language impairments, or limited mobility.

[0150] Figure 26 The supramolecularly interacting polyurethane and polyurethane-based solid ion-conducting elastomer prepared in Example 1 are applied to the demand feedback of a responsive clinical cloud webpage interaction and central monitoring platform. Figure 26 It is known that when the patient attempts to bend their thumb, the sensor output signal is captured by the system; after the platform's backend adaptive machine learning algorithm reads the underlying real-time impedance text data and performs multi-threaded parallel inference, the detection window completes baseline alignment and signal interception within an extremely short response delay, and locks the target in the voting distribution map with an absolute probability advantage of 1.0. Finally, with high confidence, the cold resistance differential signal is directly transformed into a highlighted "Result: DRINK WATER" visual care instruction on the right side of the terminal interface.

[0151] Figure 27 The supramolecularly interacting polyurethane and polyurethane-based solid ion-conducting elastomer prepared in Example 1 were applied to a responsive clinical cloud network interaction and central monitoring platform to accurately identify unknown hand gestures. Figure 27 It is evident that when an unknown finger signal is detected, the platform's backend adaptive machine learning algorithm retrieves the underlying real-time impedance text data and performs multi-threaded parallel inference. The detection window completes baseline alignment and signal interception within an extremely short response time, locking onto the target with a 93.8% prediction rate. This intelligent nursing communication paradigm, which expresses needs in a way that is silent, dignified, and personalized, not only provides patients with a way to express their needs but also offers a scalable technological platform for the future development of intelligent wards and remote care systems.

[0152] In summary, this invention provides a method for preparing supramolecularly interacting polyurethane and polyurethane-based solid ion-conducting elastomers, and their applications. The raw materials required for preparing the supramolecularly interacting polyurethane are, by weight, the following proportions: 50-200 parts of polydiol (including polydiol A and polydiol B), 100-400 parts of diisocyanate, 10-200 parts of flexible hydrazide chain extender, 10-200 parts of rigid chain extender 2-(4-aminophenyl)-5-aminobenzimidazole, 1-20 parts of dibutyltin dilaurate catalyst, and 200-500 parts of anhydrous organic solvent. The raw materials required for preparing the polyurethane-based solid ion-conducting elastomer are, by weight, the following proportions: 100 parts of supramolecularly interacting polyurethane, 10-150 parts of lithium salt, and 150-250 parts of anhydrous organic solvent. This invention has prepared a solid-state ion-conductive elastomer with excellent mechanical properties, high conductivity, low electrical detection limit, and outstanding environmental stability. Based on the conductive elastomer, a pneumatic soft gripper, a multi-cavity integrated pneumatic crawling robot, and a highly sensitive wearable strain sensor array are integrated. Furthermore, a solid-state all-soft digital medical exoskeleton rehabilitation platform and an intelligent assisted nursing interaction system have been developed by combining support vector machine algorithms, demonstrating its great potential in high-end application fields such as high-safety, high-performance flexible electronic devices and digital intelligent feedback in the future.

[0153] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

[0154] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A supramolecularly interacting polyurethane, characterized in that, The raw materials include the following parts by weight: 50-200 parts of polydiol, 100-400 parts of diisocyanate, 10-200 parts of flexible hydrazide chain extender, 10-200 parts of rigid chain extender, 1-20 parts of catalyst, and 200-500 parts of anhydrous organic solvent. The polydiol comprises polydiol A and polydiol B, wherein polydiol A and polydiol B are each independently selected from polyester diol or polyether diol, and the chemical structures of polydiol A and polydiol B are different; the rigid chain extender is 2-(4-aminophenyl)-5-aminobenzimidazole.

2. The supramolecularly interacting polyurethane according to claim 1, characterized in that, The polydiol A and polydiol B are each independently selected from any one of polytetrahydrofuran, polycaprolactone diol, polyethylene glycol, or polybutylene adipate, and the polydiol A and polydiol B have different chemical structures. The weight ratio of polydiol A to polydiol B is 0.25 to 4:1; the number average molecular weight of each polydiol is 1000 to 3000 g·mol⁻¹. -1 .

3. The supramolecularly interacting polyurethane according to claim 1, characterized in that, The diisocyanate is any one of 4,4'-diisocyanate dicyclohexylmethane or diphenylmethane diisocyanate; The flexible acylhydrazine chain extender is any one of carbohydrazine, adipic dihydrazine, sebacylhydrazine, or dodecanedicarboxylic acid dihydrazine. The catalyst is dibutyltin dilaurate; The anhydrous organic solvent is either anhydrous N,N-dimethylacetamide or anhydrous N,N-dimethylformamide.

4. A method for preparing supramolecularly interacting polyurethane as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1: Add the diisocyanate solution dropwise to the dried and dehydrated polydiol A and polydiol B, add a catalyst to carry out the prepolymerization reaction, and obtain the -NCO-terminated polyurethane prepolymer; S2: Add the flexible hydrazine chain extender solution dropwise to the polyurethane prepolymer to carry out a flexible chain extension reaction and obtain a flexible chain extended product; S3: Mix the rigid chain extender solution with the flexible chain extender product to carry out a rigid chain extension reaction. After the reaction is completed, remove the solvent to obtain the supramolecular interactive polyurethane.

5. The method for preparing supramolecularly interacting polyurethane according to claim 4, characterized in that, In step S1, the diisocyanate solution is obtained by mixing diisocyanate with anhydrous organic solvent; polydiol A and polydiol B are vacuum dried to remove water by stirring at 90~130 °C for 20~90 min; the temperature of the prepolymerization reaction is 50~85 °C and the time is 1~6 h.

6. The method for preparing supramolecularly interacting polyurethane according to claim 4, characterized in that, In step S2, the flexible hydrazide chain extender solution is obtained by mixing the flexible hydrazide chain extender with an anhydrous organic solvent; the reaction temperature of the flexible chain extension reaction is 25~50°C, and the time is 3~24 h. In step S3, the rigid chain extender solution is obtained by mixing 2-(4-aminophenyl)-5-aminobenzimidazole with anhydrous organic solvent, and the reaction temperature of the rigid chain extension reaction is 50~80 °C, and the reaction time is 3~24 h.

7. The application of a supramolecularly interacting polyurethane as described in any one of claims 1 to 3 in a soft actuator, characterized in that, The soft actuator includes a pneumatic soft gripper, a biomimetic inchworm crawling robot, and an exogenous active powered skeleton.

8. A polyurethane-based solid ion-conducting elastomer, characterized in that, The raw materials include the following parts by weight: 100 parts of supramolecular interaction polyurethane, 10-150 parts of lithium salt, and 150-250 parts of anhydrous organic solvent; wherein the polyurethane is the supramolecular interaction polyurethane as described in any one of claims 1-3. The lithium salt is any one of lithium bis(trifluoromethanesulfonyl)imide, lithium perchlorate, or lithium dioxaborate; the anhydrous organic solvent is any one of anhydrous N,N-dimethylacetamide or anhydrous N,N-dimethylformamide.

9. The method for preparing a polyurethane-based solid ion-conducting elastomer according to claim 8, characterized in that, Lithium salt, supramolecular interaction polyurethane, and anhydrous organic solvent are mixed according to the specified ratio and stirred at 40-80 °C for 5-10 h to obtain a transparent viscous solution. Subsequently, the solution is heated at 65-95 °C to remove the solvent and solidify, thereby obtaining the polyurethane-based solid ion-conductive elastomer.

10. The application of a polyurethane-based solid ion-conductive elastomer as described in claim 8 in a flexible wearable electronic device, characterized in that, The flexible wearable electronic device includes a flexible epidermal bioelectrode and a resistive sensor.

Citation Information

Patent Citations

  • Preparation method of polyacrylamide / polyurethane composite conductive hydrogel flexible sensing material

    CN120192554A

  • Composite film based on modified carbon nanotubes and thermoplastic polyurethane as well as preparation method and application of composite film

    CN121991386A